Effect of quantum phase transition on spin transport in the spatially frustrated Heisenberg model. (March 2017) - Lima, L.S.
Abstract: We have used the Schwinger's boson theory to study the spin transport in the anisotropic two-dimensional spatially frustrated Heisenberg antiferromagnetic model in the square lattice. Our results show a sudden change in the AC spin conductivity σ reg ( ω ) in the quantum phase transition point, where we have the gap of the system going to zero at critical point D c =0. We have found a sudden change for a superconductor state in the DC limit ω → 0 independent of the value of the Drude's weight found in the quantum phase transition point. Away from it, we have obtained that the behavior of the spin conductivity changes for single peak at ω = ω p and in this case, σ reg ( ω ) goes to zero in small ω and large ω limits. Abstract : Highlights: The spin current operator for the system was obtained using the discrete version of the continuity equation. The Green's function was calculated using the Matsubara's method. The components of the spin conductivity tensor was determined. Hence the AC conductivity tends to infinity when ω → 0 in the quantum phase transition points and not in other points, therefore we have a large influence of the quantum phase transition in the spin transport of this system. The inclusion of exciton-exciton interaction do not generate large influence on this result.